PENGUJIAN KINERJA HASIL RANCANGAN MENGGUNAKAN AIRFOIL K3311 (SMOOTHED) DAN GOE 549 BILAH TAPERLESS PADA HORIZONTAL AXIS WIND TURBINE (HAWT) SKALA MIKRO - Fahris Muliya (2021)
Indonesia has a very favorable geographical situation for new and renewable energy sources. Based on the National policy regarding PP No. 79 of 2014 regarding the target of renewing new energy. Wind Turbine is a renewable power plant. The blade is one of the important components in a wind turbine, where its function is to convert the kinetic energy of the wind into mechanical energy which will produce wind energy. Airfoil is the aerodynamic shape of a blade that greatly influences blade performance, in each airfoil model it has its own performance as well as K3311 (Smoothed) with GOE 549. In this research, blades for micro-scale turbines have been successfully designed, manufactured and tested. The geometry of the selected blade is taperless. The analysis was carried out on a micro-scale turbine power at a maximum wind speed of 12 m/s, a blade width of 0.12 m, 3 blades and a TSR of 7 and a linearized twist. The airfoil used has been compared to several other airfoils by simulating the Q-Blade software and comparing the results of the Cl/Cd graph to the angle of attack on each Airfoil. The simulation results show the GOE 549 bar has a maximum Cp of 0.52 at a TSR of 5.2 and K3311 (Smoothed) has a maximum Cp of 0.53 at a TSR of 5.10. The blade design is made and has passed the equilibrium test, then it is installed in a 5 meter high tower for data collection. Testing for 6 days showed that each blade produces an average power of 21.56 watts for the K3311 (Smoothed) and 32.79 watts for the GOE 549.